Effects of dietary antioxidants on oxidative stress, antioxidant defence and growth of freshwater crayfish Astacus leptodactylus (Eschscholtz, 1823) during the reproductive period in females - Barim-Oz, Ozden; Yilmaz, Seval (Wiley, 2017)
In this study, we examined the effects of dietary antioxidant vitamins [vitamin E (Vit E), vitamin C (Vit C) and vitamin A (Vit A)], astaxanthin (AX) and -carotene (C) supplementation on oxidative stress [malondialdehyde (MDA)], antioxidant enzyme activities [superoxide dismutase (SOD), catalase, glutathione peroxidase (GSH-Px)] and glutathione (GSH) levels in hepatopancreas, ovarian, muscle, gill tissues and survival rates (SR), live weight gain (LWG), specific growth rate (SGR) of Astacus leptodactylus during ovarian development. The EE, EC, EA, EAX and EC groups were formed by addingClick here to enter text. Vit E, Vit C, Vit A, AX and C to the diet respectively. The antioxidants did not have a significant impact on the values of SR, LWG and SGR. After 137days, the MDA levels in the Control (C) group were statistically higher in the hepatopancreas, ovarian and muscle tissues according negative control (NC), EE, EC, EA, EAX and EC groups. The SOD activities in ovarian, muscle and gill tissues and GSH levels in ovarian and muscle tissues were lower in the C group compared with the NC group, but GSH-Px activities in hepatopancreas and ovarian tissues and GSH levels in gill tissues were higher. The MDA levels were statistically lower in all tissues of crayfish in experimental groups according to C group. The antioxidant enzyme activities and GSH levels changed according to tissue. The results showed that Vit E and AX should be supplemented in diets to increase the reproductive performance of crayfish, because Vit E and AX were of higher potential as antioxidants than other vitamins and carotenoids in ovarian tissues.
Keywords: crayfish; oxidative stress; vitamins; carotenoids